Reconciliation as Free-Floating Signification: Reconciliation after 2014 Coup in Thailand - Sripokangkul, Siwach (Animo Repository, 2015)
The word reconciliation has become common throughout Thai society since the aftermath of the massacres of Red Shirt protesters in the heart of Bangkok in the months April and May 2010, which killed around a hundred people and injured 2,000 more. The word came into use by the government since the massacres, and has become an even more regular part of government discourse since the military’s successful May 22, 2014 coup d’état against Prime Minister Yingluck Shinawatra. The need for reconciliation stems from the incidents of national unrest created by protesters demanding Shinawatra’s resignation and the dissolution of her government between October 2013 and May 2014. In part, the military used the need for reconciliation and unity as justification for launching the coup d’état. Ever since, the military government has stated that it is creating genuine and sustainable reconciliation as well as encouraging harmony. However, the so-called reconciliation process carried out by the military government is riddled with problems. Many of the military government’s actions instead took the country back to a state in which true reconciliation in Thai society is impossible. Reconciliation as defined and deployed by the military government is inconsistent with academic definitions of reconciliation derived in the field of peace studies, due to the free-floating signification of the term. In the hands of the military government, the term reconciliation is self-paradoxical, and takes on any meaning politically beneficial to the military government. When examined more closely, it is clear that reconciliation as implemented by the military government consists of 1) creating a surveillance kingdom, 2) obliterating political opposition and threatening and hunting of people with opposing views, 3) dismantling the history of the Red Shirt movement, and 4) organizing entertainment to “return happiness” to the Thai people as a form of distraction. These so-called reconciliation activities are incompatible with the established principles of reconciliation. Above all, these forms of so-called reconciliation actually lead to the suffering of Thai advocates of democracy, and to an even more uncomfortable cultural state in Thailand, where true reconciliation is rendered even more difficult due to the suppression of honest political discourse.